EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN MEDIA GAME INTERAKTIF DIGITAL WORDWALL UNTUK MENINGKATKAN INTERAKSI SOSISAL SISWA KELAS IV SD NEGERI PRAWIT 1 SURAKARTA TAHUN 2026 - Sukmawati Dewi, Pingky; Adi Putro , Eko; Dwi Sholikhah, Linda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effectiveness of group guidance services using Wordwall digital interactive games in improving the social interaction of fourth-grade students at SD Negeri Prawit 1 Surakarta. The research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The population consisted of 58 fourth-grade students. The sample was selected through purposive sampling, resulting in 30 students with low to moderate levels of social interaction, who were divided into an experimental group and a control group, each consisting of 15 students. The research instrument was a questionnaire that had been tested for validity and reliability, supported by interviews, observations, and documentation. The data were analyzed using normality, homogeneity, and t-test analyses. The results showed that the experimental group experienced a greater improvement in social interaction scores compared to the control group. The pretest and posttest results indicated a significant difference, as shown by the Independent Samples t-test (Sig. (2-tailed) = 0.046 < 0.05 and the Paired Samples t-test (Sig. (2-tailed) < 0.001 < 0.05. These findings indicate that group guidance services using Wordwall digital interactive games are effective in improving students’ social interaction. Keywords: group guidance, Wordwall, social interaction.